Development of a Discovery Learning Model with a Meaningful Learning Approach to Improve Students' Critical Thinking Skills in Economics at SMAN 2 Tulang Bawang Udik - Dwi Prasetyo; Endang Mulyani (International Journal of Studies in International Education, 2025)
This study developed a Discovery Learning model with a Meaningful Learning approach to improve students' critical thinking skills in Economics at SMAN 2 Tulang Bawang Udik. The study used the ADDIE model and produced a conceptual model, lesson plans, student worksheets, and HOTS assessment instruments. Expert validation results showed that the products were feasible, practicality tests obtained a very practical category, and effectiveness tests with a Nonequivalent Control Group design showed that the critical thinking of students in the experimental class was higher than that of the control class. These results confirm that this learning model is feasible, practical, and effective, and can be a guide for teachers for active, contextual, and high-level thinking skills-oriented learning. Additionally, the integration of Discovery Learning and Meaningful Learning provides a structured and student-centered learning process that encourages learners to construct knowledge independently while connecting concepts to real-life contexts. The resulting learning tools also support teachers in implementing systematic instruction that fosters student engagement and deeper understanding. Overall, the developed model contributes to improving instructional quality in Economics education and offers an innovative alternative for enhancing students’ cognitive abilities, particularly in critical thinking.